2008
DOI: 10.1213/ane.0b013e3181732dc2
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Dexmedetomidine in Patients with Noninvasive Ventilation: A Preliminary Study

Abstract: This study shows that dexmedetomidine is an effective sedative drug for patients with NIV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
55
0
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 13 publications
1
55
0
6
Order By: Relevance
“…Among the agents most frequently used were benzodiazepines. In 2008, Akada et al 15 reported a preliminary study that successfully used dexmedetomidine in 10 patients to facilitate NIV tolerance. Takasaki et al 16 reported the successful treatment of 2 severe asthmatic patients with the use of dexmedetomidine to facilitate NIV.…”
Section: Discussionmentioning
confidence: 99%
“…Among the agents most frequently used were benzodiazepines. In 2008, Akada et al 15 reported a preliminary study that successfully used dexmedetomidine in 10 patients to facilitate NIV tolerance. Takasaki et al 16 reported the successful treatment of 2 severe asthmatic patients with the use of dexmedetomidine to facilitate NIV.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, the results of these studies are encouraging [7][8][9][10][11][12][13]. Overall, the use of sedation during NIV appears feasible and safe.…”
mentioning
confidence: 96%
“…In addition to the present trial [5], several observational studies [7][8][9][10][11] and three randomized trials comparing midazolam and dexmedetomidine or placebo [12][13][14] have assessed the potential use of sedative and/or analgesic drugs to reduce discomfort and risk of NIV failure. The main characteristics and results of these studies are Table 1.…”
mentioning
confidence: 99%
See 2 more Smart Citations